Sustainable Development versus Prospecting and Extraction of Shale Gas - Duda, Aneta; Gołębiowska, Justyna; Żelazna, Agnieszka (Problemy Ekorozwoju, 2016)
Energy issues are very important for our civilization. Taking into account the perspective of sustainability a lot of attention is devoted to the sources of primary Energy characterized with low emission. Among them shale gas has gained in importance as the primary energy source. The paper presents the role of shale gas in the implementation of the main paradigm of sustainable development, i.e. the intergenerational equity. As the reference, the necessity of implementing water intakes monitoring has been pointed out.